The Study of Laser Energy Effects on the Light Properties: - Zahoor Popalzai, Rokhan Mohammad (International Journal For Research In Educational Studies, 2021)
Laser is a device that emits light in the form of very thin pulses with specific wavelengths. The device is made up of a light collector or activator that is located inside the light intensity container. This substance strengthens the light source, which is created by an external source (not electricity or light). Various techniques and methods for the production of these nano-structures have been studied. The most traditional of these nano-structures are various types of shapes such as nano-rods, nano-needles, nano-pipes, nano-strand, as well as flower petal shapes monument-type structures have been created using traditional methods based on high temperatures or high vapor and chemical solutions. In this study we have shown that by changing the energy of a laser pulse or its wavelength, a collection of nanoparticles of ZnO can be produced by laser fracturing.